TAX SANCTIONS AND VEHICLE TAXPAYER COMPLIANCE: THE MODERATING ROLE OF TAX SOCIALIZATION - Fajar Muamar Fanani; Selfiani Selfiani (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study aims to analyze the influence of tax sanctions and tax socialization on the compliance of individual motor vehicle taxpayers at the Yogyakarta City SAMSAT (One-Stop Administration Service for Motor Vehicles). A quantitative approach with an associative causal design was employed. Data were collected via a structured questionnaire using a Likert scale, distributed to 100 respondents selected through simple random sampling from the population of motor vehicle taxpayers. The collected data were analyzed using multiple linear regression with SPSS to test the proposed hypotheses. The results indicate that both tax sanctions and tax socialization have a significant positive effect on taxpayer compliance, both partially and simultaneously. Partial tests (t-test) confirm that each variable individually strengthens compliance. The regression model explains 73.4% of the variance in compliance (R² = 0.734), demonstrating the strong combined explanatory power of these two factors. The findings suggest that SAMSAT authorities and similar regional institutions should adopt an integrated policy strategy. Enhancing compliance requires a dual approach that synergizes consistent and fair enforcement of sanctions with proactive, transparent, and continuous taxpayer education and outreach programs. This research contributes to the literature on behavioral taxation by empirically examining the drivers of compliance specifically among individual motor vehicle taxpayers at the regional level—a context often overlooked in prior studies focusing on corporate taxpayers. It provides actionable, evidence-based insights for designing more effective local tax administration systems.